Creating significant learning experiences : an integrated approach to designing college courses - Dee Fink, L., ....- (San Francisco : Jossey-Bass, 2013)
Since the original publication of L. Dee Fink's Creating Significant Learning Experiences, higher education has continued to move in two opposite directions: more institutions encourage faculty to focus on research, obtaining grants, and publishing, while accreditation agencies, policy-makers, and students themselves emphasize the need for greater attention to the quality of teaching and learning. Now the author has updated his bestselling classic, providing busy faculty with invaluable conceptual and procedural tools for instructional design. Step by step, Fink shows how to use a taxonomy of significant learning and systematically combine the best research-based practices for learning-centered teaching with a teaching strategy in a way that results in powerful learning experiences. This edition addresses new research on how people learn, active learning, and student engagement; includes illustrative examples from online teaching; and reports on the effectiveness of Fink's time-tested model. Fink also explores recent changes in higher education nationally and internationally and offers more proven strategies for dealing with student resistance to innovative teaching. Tapping into the knowledge, tools, and strategies in Creating Significant Learning Experiences empowers educators to creatively design courses that will result in significant learning for their students. "As thought-provoking and inspiring today as it was when it was first published, it is a 'must' for anyone serious about creating courses that challenge students to learn deeply." —Elizabeth F. Barkley, author, Student Engagement